Prevalence and factors associated with Erysipelothrix rhusiopathiae infection among raw pork handlers in Kamuli district, Eastern Uganda - Musewa, A. (2016)
Introduction: Erysipelothrix rhusiopathiae (ER) is a zoonotic, ubiquitous gram-positive bacterium, which causes erysipelas in swine, mammals, birds and erysipeloid in humans. The study was conducted in Kamuli district because farmers had reported signs of disease in their pigs which was reported at a prevalence of 67%. Therefore this study determined the prevalence and factors associated with ER infection among raw pork handlers in Kamuli district, Eastern Uganda. Methods: A cross-sectional community based study was done which employed quantitative and qualitative methods for data collection between January and March 2016. The study was conducted in Namwendwa, Bugulumbya and Kitayunjwa sub counties in Kamuli District because the farmers reported signs of the disease in their pigs. A total of 302 participants (butchers, abattoir workers and cooks) were enrolled consecutively for quantitative data collection. Participants for qualitative data collection were sampled purposively. E. rhusiopathiae infection among the handlers was determined by collecting whole blood which was used for culture and isolating the bacteria. The infection was confirmed the infection using biochemical tests and gram staining of the resulting isolates. Results: The prevalence of E.rhusiopathiae infection was 9.9 % (95% CI: 7.35 -12.52). Type of raw pork handler and alcohol consumption increased the risk of acquiring the infection. Working in the abattoir and butchery increased the risk of the infection at (aOR= 26.13 95% CI: 5.29 129.10) and (aOR= 8.37 95%CI: 1.79 -39.10) respectively. Alcohol consumption was associated with E.rhusiopathiae infection (aOR= 4.02 95%CI: 1.07 -15.03). Conclusion: The overall prevalence of E. rhusiopathiae infection was low compared to those from previous studies. Abattoir worker and butchers were highly infected with E. rhusiopathiae. Alcohol consumption, working in the abattoir and being male increased the risk of acquiring the infection. The main causes of E. rhusiopathiae were poor hygiene of the personnel especially the abattoir workers and butchers. Increased alcohol consumption among participant was associated developing the infection. Recommendations: Abattoir workers, butchers and cooks/pork buyers should be sensitized on the risk of being infected with E.rhusiopathiae infection and how to prevent it while carrying on with their duties. Raw pork handlers should avoid working under the influence of alcohol as this would impair their sense for judgment and increase their exposure to E. rhusiopathiae infection.